Literackość zamknięta w figurze retorycznej, czyli jak wyliczają reporterzy, a jak prozaicy, poeci i dramatopisarze = Literariness enclosed in a rhetorical figure. Enumeration in literary journalism, lyric poetry, prose and drama - Biernacka, Jadwiga (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Recently, literary journalism has become a critical genre of Polish literature. Its growing popularity has also resulted in a significant number of studies, comments and analyses devoted to both individual works or specific authors, as well as more universal problems concerning all representations of the genre. Among the most frequently discussed issues, one can mention the case of the literariness of reportage, acceptable (?) elements of fiction, or the boundaries of the genre. In addition, many literary and press experts also analyse reportages regarding subject matter, functions, composition or style.
Keywords: reportaż; wyliczenie; dramat; liryka; epika; wiersze; powieść; opowiadania; literary journalism; enumeration; drama; poetry; prose; poems; novel; short story